Multimodal Chronic Pain Therapy for Adults via Smartphone: Randomized Controlled Clinical Trial - Yolanda Morcillo-Muñoz; Antonio José Sánchez-Guarnido; Silvia Calzón-Fernández; Isabel Baena-Parejo (JMIR Publications, 2022)
BackgroundCombination therapies delivered remotely via the internet or mobile devices are increasingly being used to improve and promote the self-management of chronic conditions. However, little is known regarding the long-term effects of these interventions. ObjectiveThe aim of this study is to evaluate the effectiveness of a multimodal intervention program that measures associated variables such as catastrophizing, pain acceptance, and quality of life using a mobile device in people with chronic pain in an outpatient setting. MethodsA randomized controlled clinical trial was performed using parallel treatment groups. A total of 209 patients with chronic musculoskeletal pain were randomly assigned to one of the two study arms. The intervention group received a standard web-based psychosocial therapy-type program of activities through a smartphone for 6 weeks. The control group only had access to the Find out more section of the app, which contained audiovisual material for pain management based on a self-help approach. The primary outcome was catastrophizing measured using the Pain Catastrophizing Scale (PCS). Secondary outcomes were pain acceptance measured using the Chronic Pain Acceptance Questionnaire and health-related quality of life measured using the EuroQol Visual Analogue Scale. Assessments were conducted at baseline (T1), after treatment (T2), and at the 3-month follow-up (T3). The variations between the different phases were assessed using the percentage change rescaled with log base 2. The Cohen d was calculated based on the results of the linear mixed model. The investigators of the study who evaluated the results were not involved in patient recruitment and were blinded to the group assignment. ResultsPositive effects were found in the intervention group (T2-T1) in catastrophizing between the baseline and posttreatment phases (P<.001) and in helplessness (−0.72 vs 0.1; P=.002), rumination (−1.59 vs −0.53; P<.001), acceptance (0.38 vs 0.05; P=.001), and quality of life (0.43 vs −0.01; P=.002), although no significant changes were found for magnification (0.2 vs 0.77; P=.14) and satisfaction with health (0.25 vs −0.27; P=.13). Three months after treatment, significant differences were observed in the intervention group for the outcome variable of catastrophizing (PCS; −0.59 vs 0.2; P=.006) and the PCS subscales of helplessness (−0.65 vs 0.01; P=.07), rumination (1.23 vs −0.59; P=.04), and magnification (0.1 vs 0.86; P=.02). ConclusionsThe results of our study suggest that app-based mobile multidimensional treatments for adults with chronic pain improve catastrophizing, quality of life, and psychological flexibility immediately after treatment and that the effects are maintained for the primary outcome of catastrophizing for at least 3 months following treatment. Moreover, they promote self-management and can be used to complement face-to-face pain treatments. Trial RegistrationClinicalTrials.gov NCT04509154; https://clinicaltrials.gov/ct2/show/NCT04509154